if X + y – z = 2 XY – us = -3 then x² + y² + z² = ? ​

Question

if X + y – z = 2
XY – us = -3
then x² + y² + z² = ?

in progress 0
Madeline 4 days 2021-09-14T07:41:18+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-14T07:42:32+00:00

    Step-by-step explanation:

    x square = ( 2+z-y) square

    y square = (2+z-x) square

    z square = (-2-x-y)square

    so,x square + y square + z square = 16+2z square – 2y square -2X square

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )